Design and Manufacturing - Yasa, Evren; Mhadhbi, Mohsen; Santecchia, Eleonora (IntechOpen, 2020)
In product development, decisions taken in design and manufacturing are considered the most influential factors for succeeding commercialisation. Product development is a complex integrated process of several steps starting from design where the market needs are identified and turned into competitive product specifications and different design concepts. In other words, design is about identifying a problem, developing solution proposals, and validating the most feasible solution with real users. Manufacturing technologies, on the other hand, help designers to make those virtual models into physical parts by transforming different types of raw materials. This book on design and manufacturing, written by a number of experts from all over the world, presents a design perspective and different manufacturing applications from various industrial sectors.